Pegadas ambientais da alimentação e sua relação com fatores socioeconômicos e práticas de compras de alimentos: Estudo BRAZUCA Natal - Hatjiathanassiadou, Maria (2022)
Negative repercussions caused by current food systems highlight the urgency of adopting healthier and more sustainable diets. The analysis of environmental impacts from populations’ diet and eating practices can help identify solutions to achieve sustainable food, considering the environmental, social, and economic dimensions. This work aims to estimate the environmental footprints of food consumption (EFF) of people living in Natal/RN and their associations with socioeconomic characteristics and food purchase practices. Data from 411 people aged ≥20 years from the BRAZUCA Natal Study were used. Food consumption data were assessed through a Propensity Questionnaire (PQ), where the frequency of consumption of food groups was evaluated. The EFF (Water Footprint - WF, Carbon Footprint - CF, and Ecological Footprint - EF) were estimated considering standardization of 1,000 kcal/day. The relationship between socioeconomic and demographic data, food purchase practices with EFF was investigated. To verify the difference in EFF values between categories of a variable, the Mann-Whitney and Kruskal-Wallis U tests were performed. EFF was divided into tertiles (Low, Medium, and High) to assess association with other variables using Correspondence Analysis. The estimated per capita value of CF, WF and EF was 1,901.88 g CO2eq/person/day/1,000 kcal, 1,834.03 L/person/day/1,000 kcal and 14.29 m2/person/day/1,000 kcal, respectively. Meat was the food that most contributed to all three EFF, with emphasis on red meat (CF and WF) and fish (EF). The highest values of CF and WF were observed in adults, male, Caucasian, with higher per capita family income, and higher education, who had more meals in cafeterias, consumed more fast food, and used more food delivery services. Lower EFF values were observed in elderly, female, non-Caucasian, with lower per capita family income, and lower education, who had fewer meals in cafeterias, consumed less fast food, and used food delivery services less. People with the highest EFF consumed more red meat, dairy products, and ultra-processed products, while those with the lowest EFF consumed more chicken, bread, sugar, couscous, and tapioca. The findings indicate that better dietary practices were associated with lower EFF, however; it is important to highlight the relationship between lower EFF and aspects of the population’s socioeconomic vulnerability. Recognizing these relationships enables the adoption of individual and collective actions aimed at promoting healthier and more sustainable diets for all.